The Role of Digital Marketing in Expanding Rural Markets in Sub-Saharan Africa - Kiarie, John; Owusu, Ephraim; Hagabirema, Gabriel (PT. Sangadji Media Publishing, 2025)
This study investigates the role of digital marketing in expanding rural markets in Sub-Saharan Africa through a qualitative research approach. Focusing on three diverse countries—Kenya, Ghana, and Rwanda—the research involved in-depth interviews with rural entrepreneurs, digital marketing practitioners, NGO representatives, and rural consumers. The findings reveal that digital marketing significantly enhances market access, enabling rural businesses to overcome traditional geographic and infrastructural barriers. Trust-building emerged as a central factor for success, highlighting the necessity of leveraging local social networks and culturally resonant communication strategies. However, digital literacy gaps, infrastructural limitations, and socio-economic disparities pose persistent challenges to effective digital engagement. Participants demonstrated innovative adaptations to local contexts, such as the use of low-data applications and the blending of online and offline marketing efforts to maximize reach and credibility. The study contributes to the understanding of digital inclusion in emerging markets and emphasizes the need for localized, trust-centered marketing approaches. It also underlines the importance of investing in rural digital skills development and affordable connectivity to fully harness the potential of digital marketing in promoting inclusive economic growth. Despite its contributions, the study acknowledges limitations in terms of regional coverage, generalizability, and the cross-sectional nature of the research. Future studies are encouraged to adopt longitudinal and mixed-methods designs to capture the evolving dynamics of digital marketing adoption in rural Sub-Saharan Africa.